2021
DOI: 10.1002/ece3.7520
|View full text |Cite
|
Sign up to set email alerts
|

Illegal harvesting and livestock grazing threaten the endangered orchid Dactylorhiza hatagirea (D. Don) Soó in Nepalese Himalaya

Abstract: Harvesting of orchids for medicine and salep production is a traditional practice, and increasing market demand is spurring illegal harvest. Ethno‐ecological studies in combination with the effect of anthropogenic disturbance are lacking for orchids. We compared population density and structure, and tuber biomass of Dactylorhiza hatagirea (D. Don) Soó for three years in two sites: Manang, where harvesting of medicinal plants was locally regulated (protected), and Darchula, where harvesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…In this study, we explored the influences of climate change, topographical factors, and soil variables on the endangered orchid species on the QTP. We found that aspect, annual precipitation, elevation, topsoil pH (H 2 O), mean temperature of the driest quarter, and topsoil sand fraction had a large influence on the distribution of endangered orchid species on the QTP, which was in accordance with the findings of previous studies ( Chapagain et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we explored the influences of climate change, topographical factors, and soil variables on the endangered orchid species on the QTP. We found that aspect, annual precipitation, elevation, topsoil pH (H 2 O), mean temperature of the driest quarter, and topsoil sand fraction had a large influence on the distribution of endangered orchid species on the QTP, which was in accordance with the findings of previous studies ( Chapagain et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…International conventions such as the Convention on International Trade in Endangered Species of Fauna and Flora (CITES) have categorized more than 35,000 species as threatened by extinction (Wyatt 2020 ). And DNA barcodes have been demonstrated to be helpful to monitor illegal collection and trade of protected species and their products when morphological characters were equivocal (Chapagain et al 2021 ). Additionally, the risks of pandemic spillover are higher than ever with increasingly intimate associations between humans and wildlife (or their meat), some of which might serve as hosts or vectors for medically important pathogens.…”
Section: Practical Utilities Of Dna Barcodingmentioning
confidence: 99%
“…In such situations where younger generation is reluctant to peruse traditional practices, preservation of traditional knowledge and effective methods for knowledge transfer within the society, along with resource protection, become essential. Medicinal and aromatic plants growing at higher elevations are sensitive to harvest (Chapagain et al 2019(Chapagain et al , 2020Ghimire et al 2008b;Poudeyal et al 2019), and overharvesting poses a significant threat to the population of many such species in Nepal (Chapagain et al 2021, Ghimire & Nepal 2007, Ghimire et al 2005. In Khumbu Valley, harvesting of very small amount of Neopicrorhiza strictly for local use probably may not pose great threat.…”
Section: Harvesting Period/stage % Of Total Age-wise Respondentsmentioning
confidence: 99%